PRIORITAS PEMELIHARAAN IRIGASI SUB DAS KALI BRANTAS KOTA BATU MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Cholilu Rohman; Umboro Lasminto; Theresia Sri Sidharti (Journal of Civil Engineering, 2018)
This paper presents the results of the study of one of the alternative decision support systems in determining thepriority of irrigation maintenance. One of the obstacles in maintaining irrigation assets is the limited budget, hence the needfor priority maintenance of irrigation. Batu City as an agricultural area, has not applied objective assessment criteria indetermining the priority scale of irrigation asset maintenance to support the success of agriculture. Especially the irrigationarea of Kali Brantas Sub Watershed which is the downstream area of Batu City, there are still many damaged irrigationassets infrastructure. This study aims to determine the priority of irrigation maintenance of Kali Brantas Sub Watershed BatuCity. Analysis using Simple Additive Weighting method with the following stages: The assessment of each criterion directly inthe field (Physical Condition, Functioning, Service Area and maintenance cost) according to Regulation of Minister of PublicWorks No. 13 / PRT / M / 2012, , determine the rating of each alternative match, normalization of alternative value of eachcriterion and ranking of normalization product with weight of importance. The result of the analysis shows that irrigationinfrastructure which become the first priority in irrigation maintenance activity of Kali Brantas Sub Watershed Batu City isGenengan Dam. For second priority up to five consecutive are; Bend Beji I, Beji II, Ngukir Mranak II and Ngukir Mranak IDam.